Symptoms and feelings valued by patients after a percutaneous coronary intervention: a discrete-choice experiment to inform development of a new patient-reported outcome. Issue 10 (18th October 2018) - Barker, Anna L; Peeters, Geeske; Morello, Renata T; Norman, Richard; Ayton, Darshini; Lefkovits, Jeffrey; Brennan, Angela; Evans, Sue M; Zalcberg, John; Reid, Christopher; Ahern, Susannah; Soh, Sze-Ee; et al.
Abstract : Objective: To inform the development of a patient-reported outcome measure, the aim of this study was to identify which symptoms and feelings following percutaneous coronary intervention (PCI) are most important to patients. Design: Discrete-choice experiment consisting of two hypothetical scenarios of 10 symptoms and feelings (pain or discomfort; shortness of breath; concern/worry about heart problems; tiredness; confidence to do usual activities; ability to do usual activities; happiness; sleep disturbance; dizziness or light-headedness and bruising) experienced after PCI, described by three levels (never, some of the time, most of the time). Preference weights were estimated using a conditional logit model. Setting: Four Australian public hospitals that contribute to the Victorian Cardiac Outcomes Registry (VCOR) and a private insurer's claim database. Participants: 138 people aged >18 years who had undergone a PCI in the previous 6 months. Main outcome measures: Patient preferences via trade-offs between 10 feelings and symptoms. Results: Of the 138 individuals recruited, 129 (93%) completed all 16 choice sets. Conditional logit parameter estimates were mostly monotonic (eg, moving to worse levels for each individual symptom and feeling made the option less attractive). When comparing the magnitude of the coefficients (based on the coefficient of the worst level relative to best level in each item), feeling unhappy was the symptom or feeling that most influenced perception of a least-preferred PCI outcome (OR 0.42, 95% CI 0.34 to 0.51, p<0.0001) and the least influential was bruising (OR 0.81, 95% CI 0.67 to 0.99, p=0.04). Conclusion: This study provides new insights into how patients value symptoms and feelings they experience following a PCI.